Restoring degraded landscapes and sustaining livelihoods: sustainability assessment (cum-review) of integrated landscape management in sub-Saharan Africa - Birhanu, Birhanu Zemadim; Desta, Gizaw; Cofie, Olufunke; Tilahun, Seifu Admassu; Mabhaudhi, Tafadzwanashe (Frontiers in Climate, 2024)
Land degradation is a significant environmental challenge across sub-Saharan Africa. In recent decades, efforts have been undertaken, with varying successes, to rehabilitate degraded rural landscapes. However, there needs to be more evidence on the outcomes regarding enhanced productivity, environmental management, and socio-economic benefits. This study uses a case study approach, using contrasting sites from Ethiopia and Mali to appraise restoration innovations implemented through various programs. Two distinct sites were chosen from each of the study cases, and an extensive literature search was conducted to document the evidence, focusing on the sustainability gains derived from integrated landscape management (ILM). For this, the sustainable intensification assessment framework (SIAF) was used, encompassing five domains, namely productivity, economic, environmental, social, and human condition, and featuring scales from plot to landscape, all facilitated by simplified yet robust indicators such as yield, soil loss, net income, land access, and food availability. Results analyzed highlighted a higher productivity gain (35% to 55%) and an improved socio-economic benefit (>20%). The ILM in the Ethiopian highlands enabled a significant improvement in wheat and barley yield (p<0.01). Introducing new crop varieties integrated with the in-situ and ex-situ practices enabled diversifying crops across the landscape and significantly reduced runoff and soil loss (p<0.05). By increasing the cultivable land by 44%, household income was increased by selling potatoes and agroforestry products. In Mali, ILM practices reduced soil loss to 4.97t/ha from 12.1t/ha. In addition to the improvements in the yield of sorghum and maize (33% and 63%, respectively), rehabilitating the once marginal and abandoned landscape in Mali enabled landless and female-headed households to work together, improving the social cohesion among the groups. The introduction of irrigation facilities enabled widowed women to increase household vegetable consumption by 55% and increase their income by 24%. The study showed positive evidence from ILM practices in the two contrasting landscapes. However, there is a need to address challenges related to the absence of timely data monitoring and documentation of successful practices. For this, the generation of evidence-based data and the use of advanced geo-spatial tools such as Remote Sensing and GPS-installed drones are recommended.